The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ijc.32164
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and p16 immunostaining, prevalence and prognosis of squamous carcinoma of unknown primary in the head and neck region

Abstract: Science searches, observational studies and clinical trials that reported survival rates of patients with SCCUPHN by HPV status were identified. Meta-analysis estimated the prevalence and prognosis (overall survival, OS; progression-free survival, PFS) of SCCUPHN by HPV status, and compared them to studies of oropharyngeal squamous cell carcinoma (OPSCC) from the same institutions and across continents. In 17 SCCUPHN studies (n = 1,149) and 17 institution-matched OPSCC studies (n = 6,522), the pooled HPV preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
4
21
0
1
Order By: Relevance
“…The prevalence of CUP in our study was similar to that reported in other studies [10][11][12] as was the prevalence of CUP that were HPV driven. 14 Our observation that serology can identify HPV driven CUP confirms a previous report 15 and is unsurprising as they are likely to represent HPV driven OPC. Our observation that people with HPV driven CUP have improved survival is consistent with that reported in a recent meta-analysis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of CUP in our study was similar to that reported in other studies [10][11][12] as was the prevalence of CUP that were HPV driven. 14 Our observation that serology can identify HPV driven CUP confirms a previous report 15 and is unsurprising as they are likely to represent HPV driven OPC. Our observation that people with HPV driven CUP have improved survival is consistent with that reported in a recent meta-analysis.…”
Section: Discussionsupporting
confidence: 87%
“…9 A small proportion (<5%) of cancers in the head and neck present as a neck lump with no primary tumour apparent at initial presentation and are referred to as carcinoma of unknown primary (CUP). [10][11][12] A substantial proportion of people with CUP have HPV driven tumours 13,14 with an associated strong serological response 15 and better prognosis. [13][14][15][16][17] Furthermore, intensive investigation shows that CUP is often occult OPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, baseline biomarkers are evaluated for their prognostic role for disease outcomes (regardless of treatment), reflected by critical clinical trial endpoints. Key endpoints include overall survival (OS), progression‐free survival (PFS), disease‐free survival (DFS), loco‐regional (LR) control, and distant metastasis‐free survival …”
Section: Prognostic and Predictive Biomarkersmentioning
confidence: 99%
“…В Англии рак полости рта ежегодно увеличивался на 2,8% у мужчин и на 3,0% у женщин [3]. Рак орофарингеальной области является восьмой причиной смерти от рака во всем мире [4,5]. Для пациентов с карциномой орофарингеальной области ранней стадии характерна достаточно высокая пятилетняя выживаемость -82,4% [6].…”
unclassified